Antiobesity Effect of Peripheral Exendin-4 and/or Exercise in High-Fat Diet-Induced Obese C57bl/6 Mice - AL-Domi, Hayder Abdullah; Mahmud, Israa Ali (Pakistan Journal of Nutrition, 2016)
This study was conducted to examine the antiobesity effect of exendin-4 and/or exercise treatment in high-fat diet-induced obese C57BL/6 female mice and to evaluate whether these interventions could improve glucose and lipid metabolic profiles, and glucagon-like peptide-1 (GLP-1) secretion. Following the 13 weeks fattening period on the high saturated fat diet (HFSD), diet-induced obese mice continued feeding on the same HSFD and were assigned to four groups (n = 6/group); Control-Saline-Sedentary (C-Sal-Sed), Exendin-4-Sedentary (Ex-4-Sed), Saline-Exercise (Sal-Exr) and Exendin-4-Exercise (Ex-4-Exr). Mice in the exercise groups performed 13 weeks of running on a treadmill. Mice in the exendin-4 groups were injected a 100 μL exendin-4 (1 nmol/kg body weight) intraperitoneally once a day. Glucose and lipid profiles, and GLP-1 and Exendin-4 levels were determined. It was observed that sustained exposure of mice fed the HSFD for 26 weeks to exendin-4 and/or five days a week to exercise for 13 weeks resulted in a marked (p